Bedah Karya Poster Desain untuk Difabel Menggunakan Teori Semiotika - Sari Wulandari (Humaniora, 2013)
Year of 2011 was a special year for the people of Indonesia with ASEAN ParaGames held in Solo on December 12th to December 20th. Solo held ASEAN Paralympic Games in 2011 in the month of December. These special moments were used by Aikon Media, ADGI (Asosisasi Graphic Designers Indonesia), and DKV BINUS to organize a poster exhibition with works by students and lecturers of DKV BINUS University, DKV UNS Solo and Solo ADGI chapter called "Design for the disabled". The messages on the poster were addressed to the public, particularly people with disabilities who are called by "the difable" with the objective of improving people's appreciation of the difable. So that, the resulting confidence higher to those who can then deliver them to better performance. The study was conducted to see the visual signs contained in the poster work of students DKV BINUS semester 3 done by using the theory of semiotics. It can be concluded that  the communication with empathy for the disabled is the main one, and then conveyed through visual signs that have meaning and can be accepted and understood by the audience.